2016
DOI: 10.5194/acp-16-9549-2016
|View full text |Cite
|
Sign up to set email alerts
|

Parameterization of single-scattering albedo (SSA) and absorption Ångström exponent (AAE) with EC / OC for aerosol emissions from biomass burning

Abstract: Abstract. Single-scattering albedo (SSA) and absorption Ångström exponent (AAE) are two critical parameters in determining the impact of absorbing aerosol on the Earth's radiative balance. Aerosol emitted by biomass burning represent a significant fraction of absorbing aerosol globally, but it remains difficult to accurately predict SSA and AAE for biomass burning aerosol. Black carbon (BC), brown carbon (BrC), and non-absorbing coatings all make substantial contributions to the absorption coefficient of bioma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

30
170
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 175 publications
(201 citation statements)
references
References 46 publications
30
170
1
Order By: Relevance
“…We have found a trend where å abs increases with decreasing BC to OA mass ratio following an exponential function. These results are comparable to those presented by Pokhrel et al (2016) and Saleh et al (2014), with slightly lower å abs values in our study, however. This pattern could be related to a dominant presence of primary organic aerosol (POA) that has characteristically lower absorption wavelength dependence compared to SOA (Saleh et al, 2013).…”
Section: Absorption Wavelength Dependence and Brc Contributionsupporting
confidence: 76%
See 1 more Smart Citation
“…We have found a trend where å abs increases with decreasing BC to OA mass ratio following an exponential function. These results are comparable to those presented by Pokhrel et al (2016) and Saleh et al (2014), with slightly lower å abs values in our study, however. This pattern could be related to a dominant presence of primary organic aerosol (POA) that has characteristically lower absorption wavelength dependence compared to SOA (Saleh et al, 2013).…”
Section: Absorption Wavelength Dependence and Brc Contributionsupporting
confidence: 76%
“…The ratio BC to OA has been used before to parameterize å abs and ω 0 (Pokhrel et al, 2016;Saleh et al, 2014) to OA mass ratio during the North African LRT events in the wet season can be found in Fig. 11.…”
Section: Absorption Wavelength Dependence and Brc Contributionmentioning
confidence: 99%
“…These parameters include modified combustion efficiency (MCE), black carbon to organic aerosol ratio (BC / OA), and elemental to total carbon ratio ( EC EC+OC ) (Pokhrel et al, 2016;Lu et al, 2015;Saleh et al, 2014;McMeeking et al, 2014;. The current study demonstrates that the magnitude of total BrC absorption can be parameterized with the EC / OC ratio, a distinct result from Saleh et al (2014) who demonstrated that the intensive quantity of absorptivity, or imaginary refractive index, can be parameterized with the BC / OA ratio.…”
mentioning
confidence: 77%
“…Further details of the PAS calibration using the CRDS can be found in Lack et al (2012b). Further details about the instrumental setup of the PAS and CRDS can be found in Pokhrel et al (2016). The uncertainty associated with the PAS measurements during FLAME-4 was found to be 7 % (1σ ) in the 660 and 532 nm channels and 18 % (1σ ) in the 405 nm channel (Pokhrel et al, 2016).…”
Section: Pas Calibrationmentioning
confidence: 99%
See 1 more Smart Citation